Moderating Role of Cultural Values on the Relationship Among Hedonism, Materialism, and Impulse Buying : A Conceptual Framework - Sen, Shaon; Nayak, Smitha (Indian Journal of Marketing, 2021)
This paper aimed to situate the hedonism–materialism–impulse buying relationship within the theoretical frameworks of the theory of regulatory focus and the theory of social influence. Drawing from these two theories, this paper adopted the theory-building process to build a moderated mediational model that explained the mediated effect of materialism in the hedonism – impulse buying relationship. This paper also explored theoretically the moderating roles of individualism/collectivism among the constructs of hedonism, materialism, and impulse buying. This paper has contributed to the research discourse on impulse buying by showing the explanatory mechanism of a mediated moderated model.